2019
DOI: 10.15171/ijpni.2019.02
|View full text |Cite
|
Sign up to set email alerts
|

Edible seeds, leaves and flowers as Maya Super Foods: Function and composition

Abstract: Ancestral Seeds and GrainsAmaranthus cruentus L. (Amaranthceae) [Amaranth, tzets]. Although there are three main amaranth species with important seeds in the continent, this is the particularly native species of Mesoamerica. It is a pseudo cereal of low gluten content, great protein quality, and it is useful in the management of elevated glycemia, cholesterol and oxidative stress, as well as anti-cancer, hepato-and cardioprotective. 6 Its constituents include protein (albumins, globulins), essential amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
(57 reference statements)
0
2
0
1
Order By: Relevance
“…The consumption of the immature inflorescences of C. tepejilote has been a part of local culture since pre-Columbian times, as reported by Cáceres and Cruz [47], in the region dominated by the Mayan culture and linguistic family. Phytochemical food studies remain limited; although, these flowers can contribute to the Mexican diet by helping to prevent nontransmissible food-related diseases (e.g., diabetes, obesity, and metabolic syndrome), as suggested by the results reported here in terms of phenolic compounds and antioxidant activity.…”
Section: Composition Of Tepejilote Inflorescencesmentioning
confidence: 83%
“…The consumption of the immature inflorescences of C. tepejilote has been a part of local culture since pre-Columbian times, as reported by Cáceres and Cruz [47], in the region dominated by the Mayan culture and linguistic family. Phytochemical food studies remain limited; although, these flowers can contribute to the Mexican diet by helping to prevent nontransmissible food-related diseases (e.g., diabetes, obesity, and metabolic syndrome), as suggested by the results reported here in terms of phenolic compounds and antioxidant activity.…”
Section: Composition Of Tepejilote Inflorescencesmentioning
confidence: 83%
“…This study showed that the Solanaceae plant spe-cies tested possess antifungal, antibacterial, and cytotoxic activities against the organisms examined. Another species of the genus Lycianthes that has been studied is L. lycioides (L.) Hassl, it has antinociceptive and antibacterial activity due to its alkaloid content (17,28,29) .…”
Section: Species Studied Biological Activities Referencementioning
confidence: 99%
“…Similarly, there were no concentrations of heavy metals such as europium, terbium, holmium, thulium, ytterbium, lutetium and rhenium in these seeds and pods, and low concentrations of gold, hafnium, erbium, dysprosium, gadolinium, samarium and praseodymium were observed. To achieve optimal use of the products evaluated, the combined use of squash seeds, pea pods and green beans is recommended to help combat malnutrition with natural foods, to design diets for recovery of chronic patients and to prevent deficiency states in the general population (Cáceres and Cruz, 2019). These results also contribute to complete information on the chemical composition of foods or to generate databases such as the Swiss table (Switzerland, 2021).…”
Section: Toxic Trace Elementsmentioning
confidence: 99%